Photo use while dating: From forecasted photos in Tinder to creating copresence using other media - Jänkälä, Annukka; Lehmuskallio, Asko; Takala, Tapio (Human Technology, 2019)
While studying Finnish users of the online dating app Tinder searching for long-term partnerships, we paid attention to the importance of photos in their social interactions. Based on our study, we argue that photos play an important role in online dating. Initially, photos are chosen and uploaded to influence future interactions, particularly regarding who will contact them via their profile. We term this particular future tense of photography forecasted photos. Second, photos enabled the creation of copresence between dates, especially via instant messaging services instantly after capture. Third, the classic notions of photos depicting the past became important when wanting to be reminded of previous meetings. Taken together, we argue that photos enhance intimacy building while dating on social media. This role should be accounted for by paying attention not only to photography’s relation to the past or the present, but also to a future tense of photography.